2012
DOI: 10.1371/journal.pone.0047241
|View full text |Cite
|
Sign up to set email alerts
|

Is He Being Bad? Social and Language Brain Networks during Social Judgment in Children with Autism

Abstract: Individuals with autism often violate social rules and have lower accuracy in identifying and explaining inappropriate social behavior. Twelve children with autism (AD) and thirteen children with typical development (TD) participated in this fMRI study of the neurofunctional basis of social judgment. Participants indicated in which of two pictures a boy was being bad (Social condition) or which of two pictures was outdoors (Physical condition). In the within-group Social–Physical comparison, TD children used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 80 publications
1
25
0
1
Order By: Relevance
“…For example, instead of retrieving semantic representations (for personal dilemma 45 , it can be "ME HURT YOU = WRONG"), they can rely on visual imagery of the same rule, which has indeed been shown to support non-utilitarian moral judgments in healthy individuals 121 . Prior studies support this line of reasoning, e.g., a previous neuroimaging study 122 showed that typically developing children automatically encode their social knowledge into language while assessing behaviour of others in paradigms with minimum verbal requirements, but no such pattern is found in autistic children. Anecdotal reports from autistic individuals also note that they primarily rely on non-verbal thoughts 123 (as one autistic noted 122 : "I think in pictures.…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 93%
“…For example, instead of retrieving semantic representations (for personal dilemma 45 , it can be "ME HURT YOU = WRONG"), they can rely on visual imagery of the same rule, which has indeed been shown to support non-utilitarian moral judgments in healthy individuals 121 . Prior studies support this line of reasoning, e.g., a previous neuroimaging study 122 showed that typically developing children automatically encode their social knowledge into language while assessing behaviour of others in paradigms with minimum verbal requirements, but no such pattern is found in autistic children. Anecdotal reports from autistic individuals also note that they primarily rely on non-verbal thoughts 123 (as one autistic noted 122 : "I think in pictures.…”
Section: Dissociable Empathy-utilitarianism Associations Between Autimentioning
confidence: 93%
“…Thus, a simpler methodology is required, which would demand a lower level of language abilities and have less of a cognitive load, while still being a valid and reliable assessment of moral reasoning in ASD (Shulman et al, 2012). Carter et al (2012) compared children with autism (ASD) and children with typical development (TD) on the neurofunctional basis of social judgment in a fMRI study. Participants indicated in which of two pictures a boy was being bad (Social condition) or which of two pictures was outdoors (Physical condition).…”
Section: Step 5: Moral Judgementmentioning
confidence: 99%
“…We chose to decompose data into 20 components, because this is a common degree of clustering/splitting when applying ICA to rs-fMRI data (Smith et al, 2009). Selection of the components was based on their relation with social communication, resulting in the DMN (Li et al, 2014), the salience network (Toyomaki, & Murohashi, 2013), the auditory network (Russo, 2008) and the language network (Carter et al, 2012). When several components represented the same networks, the component with the highest correlation coefficient with the template was selected for further analysis.…”
Section: Independent Component Analysismentioning
confidence: 99%
“…Temporally correlated signal variations of different brain regions are thought to correspond to distinct functional resting-state networks (Beckmann, DeLuca, Devlin, & Smith, 2005). For few resting-state networks, a relation with social communication has been already demonstrated, among which the auditory network (Russo, 2008), the language network (Carter, Williams, Minshew, & Lehman, 2012), the salience network (Toyomaki & Murohashi, 2013) and the default mode network (DMN) (Li, Mai & Liu, 2014;Mars et al, 2012). Since most evidence is found on the role of the DMN in social communication, this network will be our main focus.…”
Section: Introductionmentioning
confidence: 96%